1995
DOI: 10.1093/oxfordjournals.eurheartj.a060830
|View full text |Cite
|
Sign up to set email alerts
|

Inferior ST segment depression as a useful marker for identifying proximal left anterior descending artery occlusion during acute anterior myocardial infarction

Abstract: To determine whether or not ST segment deviation on admission electrocardiograms can identify patients with anterior acute myocardial infarction due to proximal left anterior descending artery occlusion, the magnitude and location of ST segment elevation or depression were compared between patients with proximal left anterior descending artery occlusion (group A, n = 47) and those with distal left anterior descending artery occlusion (group B, n = 59). ST segment depression in each of the inferior leads was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…[8][9][10][11][12][13][14] In the present study, patients with TC showed a lower frequency of reciprocal ST-segment depression in the inferior leads compared with patients in AMI groups A and B. However, this frequency did not differ between patients with TC and patients in AMI group C, which suggests that reciprocal ST-segment depression in the inferior leads may not be useful for TC from AMI with a culprit lesions in the distal LAD.…”
Section: Comparison Of Ecg Findingsmentioning
confidence: 54%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14] In the present study, patients with TC showed a lower frequency of reciprocal ST-segment depression in the inferior leads compared with patients in AMI groups A and B. However, this frequency did not differ between patients with TC and patients in AMI group C, which suggests that reciprocal ST-segment depression in the inferior leads may not be useful for TC from AMI with a culprit lesions in the distal LAD.…”
Section: Comparison Of Ecg Findingsmentioning
confidence: 54%
“…[1][2][3][4][5][6][7] The absence of reciprocal changes, absence of abnormal Q waves, and ∑ST V4-6/∑ST V1-3 >1 have been reported as having high sensitivity and specificity for distinguishing TC from anterior AMI. 3 However, it has been hypothesized that the ECG findings of anterior AMI depend on the site of the culprit lesion and the presence of a wrapped LAD, [8][9][10][11][12][13][14][15] and therefore, we divided the present patients with an anterior AMI into groups according to the site of the culprit lesion and compared their ECG findings with those from patients with TC.…”
Section: Comparison Of Ecg Findingsmentioning
confidence: 99%
“…Previous studies showed that ST ↓ in inferior leads is a useful marker for identifying proximal LAD artery occlusion during MI [8,13,16,17]. This parameter has also been correlated with the severity of anterior wall ischemia [20][21].…”
Section: Discussionmentioning
confidence: 95%
“…Most studies have shown a poor correlation between the electrocardiogram (ECG) results and the exact extent of myocardial involvement as determined by autopsy [5,6]. In previous studies, proximal LAD artery lesion before branching S 1 (first septal branch) and/or D 1 (first diagonal branch) could be predicted by the 11 ECG parameters [7][8][9][10][11][12][13][14][15][16][17][18], namely, ST-segment depression (≥1.0 mm) in inferior leads, ST-segment elevation (≥1.0 mm) in lead aVL, ST-segment depression (≥1.0 mm) in lead aVL, ST-segment elevation (≥0.5 mm) in lead aVR, ST-segment elevation (≥2.5 mm) in lead V 1 , ST-segment elevation (<2.5 mm) in lead V 1 , STsegment elevation (≥1.0 mm) in lead V 2 , inverted U wave in lead V 1 to lead V 4 , ST-segment depression (≥1.0 mm) in lead V 5 , T inversion in lead V 4 and/or lead, and a Q wave in lead V 4 to lead V 6 . We decided to asses these ECG findings to predict whether significant lesions in the proximal LAD artery were present in patients with and without signs of anterior myocardial infarction (MI).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ST-segment depression in the inferior leads in anterior wall AMI have been shown to have a higher incidence of proximal LAD occlusion, 15,18,20,21 a larger infarct size, 4,8,12,13,19 and a poorer prognosis. 6,8,12,19 Therefore, the frequency of patients with ST-segment depression in the inferior leads could affect our results.…”
Section: St-segment Depression In the Inferior Leads Versus In The Lamentioning
confidence: 99%